Nano-encapsulated organic phase change material as thermal energy storage medium - Khadiran, Tumirah (2015)
In this study, two types of supporting materials, namely porous carbon-based material and polymer were used to encapsulate organic phase change materials (OPCM). The supporting material based on porous carbon is activated carbon (AC) derived from tropical peat soil using physical activation method (PSAC-P), AC derived from tropical peat soil using phosphoric acid (H3PO4) chemical activation method (PSAC-C) and commercial activated carbon (CAC), while supporting material based on polymer consists of mixtures of monomer styrene (St) and methyl methacrylate (MMA) at mass ratio of 4:1. The OPCM encapsulated into the pores of AC is known as shape-stabilised OPCM nanocomposite, while OPCM encapsulated into nano-sized St-MMA copolymer shell is known as OPCM nanocapsules. The shape-stabilised OPCM nanocomposite was synthesised using the one-step impregnation method, while OPCM nanocapsules was synthesised using the one-step miniemulsion in-situ polymerisation method. n-Octadecane and n-nonadecane were chosen as OPCM due to their phase transition temperatures are close to human comfort temperature (18 – 33 oC), thus they are suitable to be used for thermal comfort building applications. The latent heat and encapsulation efficiency of shape-stabilised OPCM increased as the BET specific surface area of AC increased. The increasing of latent heat and encapsulation efficiency of shape-stabilised OPCM nanocomposite are in order of shape-stabilised OPCM/PSAC-P < OPCM/CAC < OPCM/PSAC-C. The higher the BET specific area of AC, the more OPCM can be infiltrated into the pores of AC, thus increase the latent heat value. The latent heat of fusion of shape-stabilised OPCM/PSAC-P, OPCM/CAC and OPCM-PSCA-C was 95.4 J/g, 101.3 J/g and 107.2 J/g, respectively. For the encapsulation of OPCM using polymer, it was found that the mass ratio of shell to core, shell to initiator, St to MMA and thermo-chemical properties of OPCM plays an important role in the morphology, latent heat and encapsulation efficiency of the OPCM. The n-octadecane nanocapsules was successfully prepared with diameter size of 102 ± 11 nm, while n-nonadecane nanocapsules was 160 ± 16 nm. The latent heat of fusion of n-octadecane and nnonadecane nanocapsules was found to be 107.9 J/g and 76.9 J/g, respectively. Thermal cycling tests of both shape-stabilised OPCM nanocomposite and OPCM nanocapsules showed good thermal and chemical stability even after 1000 heating/cooling cycles. This indicates that both shape-stabilised OPCM nanocomposite and OPCM nanocapsules could be used as thermal energy storage (TES) medium for at least of 3 years. The shape-stabilised OPCM nanocomposite and OPCM nanocapsules with the highest latent heat was chosen as TES medium to develop thermally regulated gypsum composite board (smart gypsum composite board). The thermal performance test of thermally regulated gypsum composite boards were carried out in order to understand their ability in reducing the internal building temperature fluctuation. The results show that both shape-stabilised OPCM nanocomposite and OPCM nanocapsules play an important role in reducing the indoor building temperature, which could help to maintaining internal building comfort, thus believed could decrease the energy consumption. The results and the information generated from this study could be very beneficial to the local building industries as well as those who are concerned about internal building comfort, environmental protection and energy sustainability. All the works presented in the thesis have been accepted and published in the journals of the international repute, which reflect the quality of this research work.